2008
DOI: 10.1016/j.jasms.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A model-based method for the prediction of the isotopic distribution of peptides

Abstract: The process of monoisotopic mass determination, i.e., nomination of the correct peak of an isotopically resolved group of peptide peaks as a monoisotopic peak, requires prior information about the isotopic distribution of the peptide. This points immediately to the difficulty of monoisotopic mass determination, whereas a single mass spectrum does not contain information about the atomic composition of a peptide and therefore the isotopic distribution of the peptide remains unknown. To solve this problem a tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 6 publications
0
56
0
Order By: Relevance
“…The profile is related to the isotopic distribution of the peptide. Prior knowledge about the distribution can thus be used to develop strategies for searching for the profile in the spectra and, hence, for efficient processing of the spectral information [2][3][4][5][6]. Another application can be found in the field of metabolomics.…”
Section: Introductionmentioning
confidence: 99%
“…The profile is related to the isotopic distribution of the peptide. Prior knowledge about the distribution can thus be used to develop strategies for searching for the profile in the spectra and, hence, for efficient processing of the spectral information [2][3][4][5][6]. Another application can be found in the field of metabolomics.…”
Section: Introductionmentioning
confidence: 99%
“…[35] 2.2 Protocol-specific solutions 2.2.1 10 mM citric acid monohydrate pH 6 [29,36] ▪ 1.05 g citric acid monohydrate (Sigma-Aldrich, Japan) ▪ Dissolve in 480 mL H 2 O ▪ pH to 6.0 using 1 M NaOH (~13 mL) (Merck, Darmstadt, Germany) ▪ Make up volume to 500 mL with H 2 O 2.2.2 100 mM ammonium bicarbonate (NH 4 [32] ▪ 0.4 pmol/mL angiotensin I [34][35][36][37][38][39][40][41][42][43] ( Figure 1. Protocol for mapping the distribution and determining the identity of tryptic peptides generated in situ.…”
Section: Chemicals Consumables and Equipmentmentioning
confidence: 99%
“…SNAP using averagine [39] peptide composition) ○ Re-calibration [32] (quadratic internal re-calibration, 300 ppm tolerance using a custom mass control list [.mcl] containing the following calibrants): Figure 3. Typical MALDI-TOF/TOF spectrum (single) from an in situ acquisition (500 laser shot sum) on an FFPE ovarian cancer section prepared using the described tryptic MALDI-IMS protocol in a previous research article.…”
Section: 4mentioning
confidence: 99%
“…With a high resolution mass spectrometer such as the LTQ-Orbitrap XL, monoisotopic mass, i.e. nomination of the correct peak of an isotopically resolved group of peptides peak as a monoisotopic peak (29), is determined using an algorithm based on the study reported by Senko et al (30). These authors proposed the concept of a virtual amino acid, Averagine, constructed using the statistical occurrences of amino acids in the PIR protein data base (31).…”
Section: ϩmentioning
confidence: 99%